Framing the Predicted Impacts of COVID-19 Prophylactic Measures in Terms of Lives Saved Rather Than Deaths Is More Effective for Older People - Pietro Biroli; Steven J. Bosworth; Marina Della Giusta; Amalia Di Girolamo; Sylvia Jaworska; Jeremy Vollen (Institute of Labor Economics (IZA), 2020)
This paper contributes to the literature on public health communication by studying how the framing of a message relaying the forecast impact of COVID-19 prevention measures affects compliance behaviour amongst both the young and old. A representative sample of survey respondents in the UK and US, along with selected respondents in Italy, were presented with forecasts for the number of deaths from COVID-19 in their countries with and without public adherence to various preventive behaviours. We experimentally varied whether this information was presented in terms of likely deaths or lives saved. The lives saved frame increases reported protective behaviours, but only amongst older respondents. We present evidence consistent with the hypothesis that framing is likelier to affect decisions whose consequences are felt by oneself (i.e. protective behaviours by the elderly) rather than solely others (i.e. protective behaviours amongst the young).
Keywords: D03; D83; D84; D85; J16; J24; 330; framing; protective behaviours; cooperation; age; gender; COVID-19